Timing of Frontal Plane Trunk Lean, Not Magnitude, Mediates Frontal Plane Knee Joint Loading in Patients with Moderate Medial Knee Osteoarthritis - Freyja Hálfdanardóttir; Dan K. Ramsey; Kristín Briem (Advances in Orthopedics)
The purpose of this study was to examine the influence of trunk lean and contralateral hip abductor strength on the peak knee adduction moment (KAM) and rate of loading in persons with moderate medial knee osteoarthritis. Thirty-one males (17 with osteoarthritis, 14 controls) underwent 3-dimensional motion analysis, strength testing of hip abductors, and knee range of motion (ROM) measures, as well as completing the knee osteoarthritis outcome score (KOOS). No differences were found between groups or limbs for gait cycle duration, but the osteoarthritis group had longer double-limb support during weight acceptance (p<0.001) and delayed frontal plane trunk motion towards the stance limb (p<0.01). This was reflected by a lower rate of loading for the osteoarthritis group compared to controls (p<0.001), whereas no differences were found for peak KAM. Trunk angle, contralateral hip abductor strength, and BMI explained the rate of loading at the involved knee (p<0.001), an association not found for the contralateral knee or control knees. Prolonged trunk lean over the stance limb may help lower peak KAM values. Rate of frontal plane knee joint loading may partly be mediated by the contralateral limb’s abductor strength, accentuating the importance of bilateral lower limb strength for persons with knee osteoarthritis.